تقدير وثوقية نظام توليد الطاقة الكهربائية - أحمد الحسن الناصر (Tishreen University, 2019)
تقدم هذه الورقة مدخلاً عاماً من أجل تحديد نموذج ماركوف للأنظمة المحييّطة، والذي على أساسه تم تحديد نموذج ماركوف للوثوقية من أجل محطات التوليد المزودة بوحدات توليد احتياطية جاهزة (احتياطي ساخن، ظاهر أو سري) redundant standby aparent or secret سواء كانت هذه الوحدات قابلة للإصلاح أو غير قابلة الإصلاحreparable or non- reparable. وأخيرا تم تقديم تحليل  كمي لوثوقية محطات التوليد المزودة بالاحتياطي المذكور redundant standby  في كل من حالة النظام القابل للصيانة وحالة النظام غير القابل للصيانة، بحيث يظهر أثر الصيانات على رفع وثوقية محطات التوليد المذكورة.   In this paper, a general approach to establishing the Markov reliability model of the redundant systems is presented. On the basis of this approach, the Markov reliability model of generating stations is determined, which are watered with non-repairable or repairable standby redundant generating units. Finally, a quantitative reliability analysis of the two-component standby redundant units generating station is performed. The analysis indicates that repairing has a very significant influence on the reliability increase of these stations.